Hybrid concentrated photovoltaic thermal technology for domestic water heating - M. K.Panjwani; S. X. Yang; F. Xiao; K. H. Mangi; R. M. Larik; F. H. Mangi; M. Menghwar; J. Ansari; K. H. Ali (Institute of Advanced Engineering and Science, 2019)
There is an increasing reliance on renewable energy especially Solar Energy as the fossils are on the way to depletion.It offers an environmental friendly solution with an affordable comparative paradigm. Solar photovoltaic-thermal collectors have remained of the particular interest because of their higher overall efficiencies. Most of its applications related with solar hybrid PVT systems focuses more on electrical output rather than thermal output, and the contacting fluid is allowed to act as a coolant to assure that the solar cell operates in the ranges specified by the manufacturer to guarantee higher electrical efficiency. This ultimately allows fluid to retain higher temperature that could be utilized for meeting the heating demand of any residential household. First, the PVT analyses are performed over a system comprising of Fresnel-based Solar Module to allow higher irradiance to fall for relative higher conversion of efficiency and to achieve higher temperature ranges in the contacting fluid (water). The electrical parameters are compared, and a significant increase in the power ranges is concluded. Secondly, a simulated thermal structure of the heating tank is presented that utilises the heated water from the PVT system in meeting the heating demand of a residential household. When accounting all the electrical parameters, approximately 10% increase is noticed in power produced, and sufficient energy used for the traditional heating of water is retained.